Job quality in triadic employment relations: Work attitudes of Norwegian temporary help agency employees - Kalleberg, Arne L.; Nesheim, Torstein; Olsen, Karen M. (Scandinavian journal of management, 2015)
•We examine job quality among employees of temporary help agencies (THA).•We assess how triadic employment relations influence work attitudes.•Job quality is greater when the employees are valuable to the client-firm.•Conflicting signals from THAs and clients reduce job satisfaction.•Preferences for temporary work are strongly associated with job satisfaction. In this article we examine job quality and job satisfaction among employees of temporary help agencies (THAs) in Norway. Temporary workers are subject to triadic employment relations as they are employed by the THA but directed by the client organization; characteristics of both of these organizations may affect job satisfaction directly and indirectly through job rewards. Our data are based on a survey of a representative sample of workers employed by THAs (N=2678). We find that job quality is greater when: agency workers possess an asset that is valuable to the client firm; there are not conflicting demands on the temporary worker from the THA and the client firm; and employees prefer to work as temporaries. Autonomy, pay satisfaction, intrinsic rewards, and security are associated with job satisfaction after controlling for the features of triadic employment relations.